(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Physical activity is one of the triggers to sustainable economic and social development of societies. The Political Declaration of the 2030 Agenda reflects on “the contribution sports make to the empowerment of women and of young people, individuals and communities, as well as to health, education and social inclusion objectives” [1]. COVID-19 restrictions forced the industry to find new ways to organize interregional and international events and find the ways out of the sudden crisis [2]. In this paper, authors focus on analysis of physical activity and sports recovery process after COVID-19 pandemic that has created profound challenges for youngsters and their family members. This research relies on empirical data collected from main orienteering sports events in Latvia and demonstrates original forecast model that compliments existing system dynamic simulation models affected by COVID-19 situation with respect to increased level of digitalization and extensive use of technologies. Research outcomes demonstrate that the cancellation of sports activities negatively affects such social aspects as people mobility, social cohesion, emotional satisfaction and excitement. As follows, it leads to lower physical and mental activity for individuals, especially children and youth. At the same time, the research outcomes of authors’ developed system dynamics simulation model shows that a recovery process of analysed physical activity and sports events is reasonably fast and, in the most cases, in two years reached a level of pre-COVID-19 period with tendency to positive growth in future. Created original system dynamic simulation model embraces full data sets of ten years (2014-2023), extracted from orienteering sports events published data in Latvia, as well as outcomes of several practical testing and theoretical research activities in Latvia and Albania. For collection and systemization of empirical data, authors used the concept of “Citizen Science”. The Citizen Science is an ever-growing field of public engagement with science, and recent years have seen an increasing number of studies examining its potential [3]. The conclusions, made by authors of this research, are useful for various sports and active lifestyle events’ organizers, supporters, spectators and others, involved in the organization process of physical activity and sports events to attract more participants, spectators and tourists to their areas.